Iron Deficiency Anemia in Patients with Chronic Renal Insufficiency at Tertiary Care Hospital in Northern Punjab: Iron Deficiency Anemia in Chronic Renal Disease - Shuaib, Muhammad; Imran, Muhammad; Khan, Hasan Akbar; Ikram ul Haq, Muhammad; Zubair, Hafiz Muhammad; Irfan, Muhammad (Pakistan Journal of Health Sciences, 2024)
Anemia is a frequently encountered complication of chronic kidney disease (CKD) leading to worse outcomes in terms of quality of life and premature death. However, the current prevalence of iron deficiency anemia (IDA) in CKD is understudied in Pakistan. Objective: To assess the frequency of IDA in patients with CKD at Bewal International Hospital, Gujar Khan, Pakistan. Methods: A cross-sectional was executed at the Department of Nephrology, Bewal International Hospital, Pakistan from January 1, 2022, to June 30, 2022. The study comprised 97 patients aged >13 years of either gender having CKD (GFR <60 ml/min/1.73m²) for at least 90 days. All patients were tested for serum creatinine, ferritin, and hemoglobin levels. IDA was considered if hemoglobin was ≤12 mg/dL in women and ≤13 mg/dL in men. Results: Among 97 patients, there were 57(58.7%) males and 40(41.3%) females. The mean age was 51.23 ± 12.99 years while the mean disease duration was 6.01 ± 1.610 years. 57(58.7%) patients had IDA. IDA was more frequent in women with CKD (67.5%), compared to men (52.64%). However, this association was statically insignificant (p>0.05). When data was stratified, a substantial association was found between IDA and the stage of CKD (p=0.007). There was no significant association between IDA and disease duration (p>0.05). Conclusions: It was concluded that anemia is common in CKD patients, with a high prevalence in females. Stage 3–5 CKD is significantly associated with developing iron deficiency anemia. Early identification and timely management can avoid unfavorable outcomes in these patients.